TRIM33 gene somatic mutations identified by next generation sequencing in neoplasms of patients with anti-TIF1γ positive cancer-associated dermatomyositis. (25th March 2021) - Cordel, Nadège; Derambure, Céline; Coutant, Sophie; Mariette, Xavier; Jullien, Denis; Debarbieux, Sébastien; Chosidow, Olivier; Meyer, Alain; Bessis, Didier; Joly, Pascal; Mathian, Alexis; Levesque, Hervé; et al.
Abstract: Objective: To deep sequence the TRIM 33 gene in tumours from patients with cancer-associated anti-TIF1γ autoantibody-positive dermatomyositis (DM) as TRIM33 somatic mutations in tumours may trigger this auto-immune disease. Methods: Next generation sequencing of tumour DNA samples from patients with cancer-associated anti-TIF1γ autoantibody-positive DM. Fourteen tumours from 13 anti-TIF1γ autoantibody-positive DM individuals were sequenced along with two control tumours from non-DM individuals. Results: Fourteen probable somatic variants from four tumours were identified in the TRIM33 gene. Conclusion: These results are in accordance with the previous report of Pinal-Fernandez et al. and support the hypothesis of a role of TRIM33 gene mutations in the pathophysiology of anti-TIF1γ autoantibody-positive DM.